UGC Newsletter Green@UiTM Volume 1, Jan-June 2025 - UiTM, UGC (UiTM Green Centre, 2025)
The UGC Newsletter Green@UiTM Volume 1, Jan-June 2025 highlights the university’s initiatives, innovations, and community efforts in promoting environmental stewardship, energy efficiency and sustainable campus agenda.